Hubungan Perilaku Konsumsi Zat Besi Dengan Kejadian Anemia Pada Ibu Hamil di Klinik Bidan Ade Irma Batubara Tahun 2023 - Fitri Mayasari Panggabean; Sri Rezeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Efforts to prevent and control iron nutritional anemia are prioritized for pregnant women by providing iron supplements. Iron consumption and variations in the amount of iron intake during pregnancy in East Java are 99.4%. The aim of the research is to determine the relationship between iron consumption and the incidence of anemia in pregnant women at the Ade Irma Batubara Midwife Clinic in 2023.The type of research carried out was Descriptive Analytical with a cross sectional approach, the population in the study was 20 people using Total Sampling. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square.The research results showed that the majority of respondents had sufficient knowledge, 9 (45%) respondents with moderate anemia with a Chi square of 0.0005. The majority of respondents behaved less, as many as 14 (70%) respondents had moderate anemia with a chi square of 0.001. The majority of respondents had a poor attitude, 14 (70%) respondents with moderate anemia with a chi square of 0.000.The conclusion is that there is a relationship between iron consumption and the incidence of anemia in pregnant women at the Ade Irma Batubara Midwife Clinic in 2023. It is hoped that all health workers at the Ade Irma Batubara Midwife Clinic will be more active in looking at iron consumption and the incidence of anemia in pregnant women.